Monocytes in inflammatory bowel disease: absolute monocyte counts. - Mee, A; Berney, J; Jewell, D (BMJ Publishing Group, 1980)
Using a cytochemical staining technique, peripheral blood monocytes have been precisely identified and enumerated in patients with inflammatory bowel disease and compared with healthy and disease control subjects. For ulcerative colitis there was a significant monocytosis, which was closely correlated with the total white cell count and with the activity of the disease. For patients with Crohn's disease, the peripheral blood monocyte count was also raised compared with that of the control groups, but the difference did not reach statistical significance. There was no correlation between the monocyte count in patients with Crohn's disease and the total white cell count or the disease activity. Some of the mechanisms that may influence the production and distribution of peripheral blood monocytes are discussed.